Urban projects in France: navigating neoliberalism, justice, and commons planning - Youness Achmani (Discover Sustainability)
Abstract This review paper examines the concept of urban projects within the evolving landscape of urban planning theory and practice, with a particular focus on the French context. Through a targeted review of French and English language literature, we trace the development of planning models from rational comprehensive approaches to more collaborative and strategic models. We argue that the urban project emerges as a multifaceted construct, embodying processes, outcomes, and actor-rules dynamics. The paper explores three key research subjects in contemporary urban projects: the interplay between neoliberal and the just city paradigms, the divergence between judicial and spatial understandings of justice, and the potential of commons and social innovation as an emerging paradigm and a response to neoliberal paradigm and spatial inequalities. This research synthesises existing knowledge and identifies key areas for future investigation, offering insights that can inform both theoretical discourse and practical applications in urban planning.